Arid zone is a treasure trove of indigenous and minor vegetables - Saroj, P L; Choudhary, B. R. (Indian Horticulture, 2020)
The hot arid zone possesses wide range of genetic diversity among several annual and perennial vegetables. The crops indigenous to arid region are capable to withstand biotic stresses and possess several medicinal properties. The ICAR-Central Institute of Arid Horticulture, Bikaner, Rajasthan is continuously making the efforts for collection, evaluation, maintenance, conservation and utilization of germplasm available in arid zone. Being drought and high temperature tolerant, the varieties developed by the institute are popular among the farmers of arid zone and making strident.